PENDAMPINGAN PENERAPAN MANAJEMEN PEMBELAJARAN BERBASIS MULTIPLE INTELLIGENCES DI SMA KECAMATAN WAY JEPARA KABUPATEN LAMPUNG TIMUR - Jamiluddin Yacub (LPPM STAI DARUSSALAM LAMPUNG, 2021)
This study aims to describe, reveal, and find the dominant factors of multiple intelligence-based learning management in improving learning achievement in the field of life skills. The focus of this research is on planning, organizing, implementing, evaluating, and learning outcomes. This study uses a qualitative design with a naturalistic approach and based on constructivism, which views reality as having multiple dimensions, data were collected through interviews, observation, documentation, and triangulation. The results of this study conclude that multiple intelligence-based learning management is very effective for fulfilling students' life skills, that each student can develop their respective types of intelligence in various ways, intelligence is not only limited to IQ, but there are other intelligences including linguistic intelligence, Mathematical logic, spatial, kinesthetic, musical, interpersonal, intrapersonal, and naturalistic. Learning management based on multiple intelligences begins with MIR (multiple intelligences research for each new student as the basis for preparing lesson plans. The learning implementation is preceded by apperception containing alpha zones in the form of special greetings, fun stories, ice breaking, or singing. The core activities consist of exploration, elaboration, and singing). confirmation, apperception exploration in the form of warmer, pre-teach, and scene setting, elaboration containing learning strategies and methods, while confirmation in the form of teacher and student questions and answers to determine lesson acceptance, Evaluation by means of authentic assessment which includes three domains of knowledge (cognitive) consisting of tests daily, UTS, UAS, annual test, attitude (affective) assessment of teachers, self, friends, and anecdotal records, assessment of skills (psychomotor) in the form of performance (performance), work (product), and making projects (project). The obstacle to learning management based on Multiple Intelligences is changing the paradigm a teacher, making lesson plans, choosing varied learning strategies, and conducting authentic student assessments.